2013
DOI: 10.1159/000346783
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Error-Monitoring Function in People with Internet Addiction Disorder: An Event-Related fMRI Study

Abstract: Background: Internet addiction disorder (IAD) is rapidly becoming a prevalent mental health concern around the world. The neurobiological underpinnings of IAD should be studied to unravel the potential heterogeneity. This study was set to investigate the error-monitoring ability in IAD subjects. Methods: Fifteen IAD subjects and 15 healthy controls (HC) participated in this study. Participants were asked to perform a fast Stroop task that may show error responses. Behavioral and neurobiological results in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 58 publications
1
52
2
1
Order By: Relevance
“…In the last 10 years, however, most researchers in this field have used the term “Internet addiction” or “Internet addiction disorder” (e.g., Johansson and Götestam, 2004; Block, 2008; Byun et al, 2009; Dong et al, 2010, 2011, 2013; Kim et al, 2011; Purty et al, 2011; Young, 2011b, 2013; Young et al, 2011; Zhou et al, 2011; Cash et al, 2012; Hou et al, 2012; Hong et al, 2013a,b; Kardefelt-Winther, 2014; Pontes et al, 2014; Tonioni et al, 2014). We also prefer the term “Internet addiction (IA),” because recent articles (see discussion in Brand et al, 2014) highlight the parallels between an overuse of the Internet and other addictive behaviors (e.g., Grant et al, 2013) and also substance dependency (see also Young, 2004; Griffiths, 2005; Meerkerk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the last 10 years, however, most researchers in this field have used the term “Internet addiction” or “Internet addiction disorder” (e.g., Johansson and Götestam, 2004; Block, 2008; Byun et al, 2009; Dong et al, 2010, 2011, 2013; Kim et al, 2011; Purty et al, 2011; Young, 2011b, 2013; Young et al, 2011; Zhou et al, 2011; Cash et al, 2012; Hou et al, 2012; Hong et al, 2013a,b; Kardefelt-Winther, 2014; Pontes et al, 2014; Tonioni et al, 2014). We also prefer the term “Internet addiction (IA),” because recent articles (see discussion in Brand et al, 2014) highlight the parallels between an overuse of the Internet and other addictive behaviors (e.g., Grant et al, 2013) and also substance dependency (see also Young, 2004; Griffiths, 2005; Meerkerk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In China, arguably the most important subtype of IAD may be IGD (Dong et al, 2011a, 2012, Dong et al, 2013c). One key feature of IGD is lost or diminished self-control over participation in Internet game-playing.…”
Section: Introductionmentioning
confidence: 99%
“…Executive function enables individuals to inhibit their desires and limit engagement in hedonic behaviors under unfavorable circumstances (Everitt et al, 2007, Goldstein and Volkow, 2011, Dong et al, 2013a, Sofuoglu et al, 2013, Lin et al, 2014a). Behavioral and/or brain differences between IGD and healthy controls have been observed during task performance on go/no-go (Dong et al, 2010), attention bias (Ko et al, 2013), set-shifting (Zhou et al, 2012, Dong et al, 2014), Stroop (Dong et al, 2011c), and error-processing (Dong et al, 2013c) tasks. Together, these data provide a neurobiological explanation for behavioral control difficulties that individuals with IGD often exhibit.…”
Section: Introductionmentioning
confidence: 99%
“…Greater activity in the ACC was also revealed for the interference condition of the stroop paradigm (Dong et al, 2012b) and a meta-analysis showed that IAD had a significant hyperactivation in medial frontal/ACC (Meng et al, 2014). Subjects with IAD also demonstrated an impaired error monitoring ability compared to controls, which was related with the stronger activity in dorsal ACC in error responses (Dong et al, 2013a). Behavior studies showed that IAD individuals were associated with longer reaction time and more response errors in incongruent conditions than the controls without IAD (Dong et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In brief, it is consistently shown that the prefrontal cortex (PFC) and striatum are implicated in IAD. Subjects with IAD have reduced gray matter densities/volumes (Yuan et al, 2011; Zhou et al, 2011; Weng et al, 2013), cortical thickness (Hong et al, 2013a; Yuan et al, 2013), glucose metabolism (Tian et al, 2014) and altered brain activation (Dong et al, 2013a; Ko et al, 2014) in the PFC including the dorsolateral PFC, orbitofrontal cortex (OFC) and anterior cinguate cortex (ACC). IAD addicts were also found to have lower level of dopamine D2 receptors (Kim et al, 2011; Hou et al, 2012), altered glucose metabolism (Park et al, 2010a) and brain activation (Ko et al, 2014; Li et al, 2014) in the striatum.…”
Section: Introductionmentioning
confidence: 99%